2015
DOI: 10.1007/s12031-015-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from Dendritic Cells Loaded with Chaperone-Rich Cell Lysates Elicit a Potent T Cell Immune Response Against Intracranial Glioma in Mice

Abstract: Chaperone-rich cell lysates (CRCLs) may play an important role in the development of anti-tumor vaccines. Tumor-derived CRCLs have been reported to activate dendritic cells (DCs) to elicit potent anti-tumor activity. However, the role of DC-derived exosomes (DEXs) secreted from DCs loaded with CRCLs in the treatment of tumors has not been clearly determined. In the present study, DEXs were generated from DCs loaded with CRCLs derived from GL261 glioma cells. These DEXs, designated DEX (CRCL-GL261), were then u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…It is found that exosomes released from glioma cells have the potency to act as antigen sources for immune system activation ( 99 ). Experiments conducted with dendritic exosomes revealed its anti-tumor activity by the induction of T-lymphocytes ( 100 ). Anti-cancer immunity of DC-derived exosomes has also proved in B16F10 melanoma model ( 101 ).…”
Section: Exosomes As Diagnostic Agents or In Cancer Therapeuticsmentioning
confidence: 99%
“…It is found that exosomes released from glioma cells have the potency to act as antigen sources for immune system activation ( 99 ). Experiments conducted with dendritic exosomes revealed its anti-tumor activity by the induction of T-lymphocytes ( 100 ). Anti-cancer immunity of DC-derived exosomes has also proved in B16F10 melanoma model ( 101 ).…”
Section: Exosomes As Diagnostic Agents or In Cancer Therapeuticsmentioning
confidence: 99%
“…Curiously, CRCL has strong proteomic overlaps with exosomes, and has a novel structure that may lead to similar DC responses as TEX [ 81 ]. In a similar set of experiments, but using syngeneic DEX from CRCL-pulsed DCs in the same murine brain tumor model, those DEX drove CBL (Cbl proto-oncogene, E3 ubiquitin protein ligase) and CBLB (Cbl proto-oncogene B, E3 ubiquitin protein ligase) signaling with AKT (protein kinase B) and ERK (extracellular regulated kinase) signaling in stimulated T cells [ 82 ].…”
Section: Exosomes As Potential Vaccine Candidates (All Hands On Dementioning
confidence: 99%
“…Moreover, tumor-derived chaperon rich cell lysates containing Hsp70, Hsp90, calreticulin, and glucose-regulated protein 94 have been reported to activate DCs (58). Bu et al (59) demonstrated that exosomes from DCs loaded with chaperone-rich cell lysates could elicit a potent T cell immune response against intracranial glioma in mice. These findings suggested that chaperons are potent candidates to increase the immunostimulatory effect of TEXs.…”
Section: Hsp70/90 Overexpression (Heat Treatment)mentioning
confidence: 99%